The use of Learning Management System on University Students’ Vocabulary Mastery - Ifit Novitasari; Eko Aprianto; Dwi Fita Heriyawati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2018)
The development of learning media that is interesting and relevant to the education system in Indonesia, although the ability of learners is a barrier today. Various development efforts are always done to complement the process of material oblivion that has been given. Learning methods and learning media are two things that cannot be ignored. Having English skills will add value in the context of human resources. But in an academic environment, English is a foreign language that needs to be mastered not only in communication but also regarding technology and science. The increasingly rapid technological development takes part in the learning development system. Many learning media are used to improve the ability of information or science. Furthermore, this study uses a learning management system (LMS) as one of the technology media to improve students’ vocabulary. The study focuses on the effort to improve vocabulary mastery by using a learning management system. The subjects of this study were the second-semester students from informatics department, Universitas Kanjuruhan Malang. The results of this study show that the students are easier to understand the vocabulary used in technology informatics fields. It can be seen that the results of their average of the final score are 85.00 improved higher than the previous score, before the use of LMS in the teaching vocabulary, the score is 65.00. It is expected that the result of this study can be one of the alternative ways to help students understand vocabulary easily.